Patient perception of junior interns’ professionalism in teaching hospital - Taufan, Ali; Grace, Aprilia; A Nugraha, Biancha (ACTA Medical Health Sciences, 2024)
A doctor's professionalism consists of clinical competence, communication skills, ethical and legal understanding, accountability, altruism, excellence, and humanism, of which the seven pillars of professionalism are applied at the professional level. This research aimed to describe patient perceptions of the professionalism of junior interns at Dustira Teaching Hospital. Data collection occurred in November-December 2022. This research utilized a quantitative approach, employing a descriptive research method with a cross-sectional design. The study results, which included patient characteristics such as age, sex, education level, and length of stay based on the seven pillars, showed the following outcomes: clinical ability (97.6%), communication skills (95.4%), understanding of ethics and law (92%), accountability (94.8%), altruism (90.8%), and excellence (94.4%) all fell within the very good category. In contrast, the aspect of humanism (66.2%) was only rated as quite good. Researchers suggest that institutions and junior interns should re-evaluate the learning and application of the professionalism among junior interns. While aspects of humanism are generally considered positive, there is still room for improvement. Therefore, further learning and re-evaluation regarding the professionalism aspect of humanism can be beneficial. DOI : 10.35990/amhs.v3n2.p75-83 REFERENCES Kanter, M. H., Nguyen, M., Klau, M. H., Spiegel, N. H., & Ambrosini, V. L. (2013). What does professionalism mean to the physician? The Permanente Journal, 17(3), 87–90. Mueller, P. S. (2015). Teaching and assessing professionalism in medical learners and practicing physicians. Rambam Maimonides Medical Journal, 6(2), e0011. Epstein, R. M., & Hundert, E. M. Defining and assessing professional competence. Retrieved from jama.com Tsugawa, Y., Tokuda, Y., Ohbu, S., Okubo, T., Cruess, R., Cruess, S., et al. (2009). Professionalism mini-evaluation exercise for medical residents in Japan: A pilot study. Medical Education, 43(10), 968–978. Undang-Undang Republik Indonesia Nomor 44 Tahun 2009 tentang Rumah Sakit. (2009). American Board of Internal Medicine. (n.d.). Project Professionalism: Promoting Excellence in Health Care. Retrieved from abim.org Mueller, P. S. (2009). Incorporating professionalism into medical education. Division of General Medicine and Program in Professionalism and Bioethics, Mayo Clinic, 1–11. Alizamar, & Couto, N. (2016). Psikologi Persepsi & Desain. Media Akademi. Rosenstein, A. H., & O’Daniel, M. (2008). A survey of the impact of disruptive behaviors and communication defects on patient safety. The Joint Commission Journal on Quality and Patient Safety, 34(8), 464–471. Papadakis, M. A., Teherani, A., Banach, M. A., Knettler, T. R., Rattner, S. L., Stern, D. T., et al. (2005). Disciplinary action by medical boards and prior behavior in medical school. New England Journal of Medicine, 353. Retrieved from nejm.org Purwanti, M., Armyanti, I., & Asroruddin, M. (2020). Persepsi mahasiswa Fakultas Kedokteran Universitas Tanjungpura mengenai konsep profesionalisme dokter. Nurlina, A., Dewi, M. K., Rachmi, A., Indrasari, E. R., & Kusmiati, M. (2019). Persepsi dokter pendidik klinis terhadap perilaku profesional dokter muda di Rumah Sakit Pendidikan Fakultas Kedokteran Unisba. Jurnal Integrasi Kesehatan & Sains, 1(2). Saleh, A. A. (2018). Pengantar Psikologi. Sidenreng Rappang: Aksara Timur. Rakhmat, J., & Surjaman, T. (2001). Psikologi Komunikasi. Bandung: PT Remaja Rosdakarya. Sarwono, S. W. (2009). Pengantar Psikologi Umum (E. A. Meinarno, Ed.). Depok: Rajagrafindo Persada. Ariardi, H. (2005). Persepsi pasien terhadap mutu pelayanan dokter ditinjau dari karakteristik dan mutu pelayanan dokter di instalasi rawat jalan RSI Sunan Kudus. [Skripsi, Universitas Diponegoro]. Valderas, J. M., World Health Organization. (n.d.). Patient Engagement. World Health Organization, Department of Service Delivery and Safety. Peraturan Menteri Kesehatan Republik Indonesia Nomor 4 Tahun 2018. (2018). Rahmah, F. (2016). Hubungan antara jenis kelamin dan usia dengan persepsi pasien terhadap komunikasi dokter di Puskesmas Pakisaji Kabupaten Malang. [Diakses 27 Agustus 2022]. Peraturan Menteri Kesehatan Republik Indonesia Nomor 290 Tahun 2009 tentang Persetujuan Tindakan Kedokteran. Rahayu, S. (2021). Tinjauan length of stay (lama rawat). Makassar. Windiyani, T., Kurnia, D., & Purnamasari, R. (n.d.). Studi Pendidikan Guru Sekolah Dasar. Edisi pertama. Universitas Pakuan. Pudjosumedi, Handayani, T., Saidah, E. S., & Istaryatiningtias. (2013). Buku Profesi Pendidikan. Jakarta: UHAMKA Press. Amin, Y. (2017). Etika Profesi dan Hukum Kesehatan (Suparmi & Junianti Heru, Eds.). Kementerian Kesehatan Republik Indonesia, hlm. 18–23. Ananda, R. (n.d.). Profesi Pendidikan. Arnold, L. (n.d.). Assessing professional behavior: Yesterday, today, and tomorrow. Academic Medicine. Kusumawati, W. (2011). Profesionalisme dan professional behavior mahasiswa. Mutiara Medika, 11(1), 37–45.